11-OH-THC in hair as marker of active cannabis consumption: Estimating a reliable cut-off by evaluation of 672 THC-positive hair samples. (November 2019) - Casati, Sara; Angeli, Ilaria; Ravelli, Alessandro; Del Fabbro, Massimo; Minoli, Mauro; Orioli, Marica
Highlights: The identification of THC-COOH in hair will continue to be challenged. 11-OH-THC may be considered as a complementary marker for THC administration. ROC analysis was applied for cut‐off evaluation after 11-OH-THC quantification (n = 672). Abstract: Hair analysis for the assessment of cannabis active use from passive consumption may be failed when performed by the sole detection of compounds present in plant material as well as in cannabis smoke like Δ‐9‐tetrahydrocannabinol (THC), cannabidiol (CBD), and cannabinol (CBN). For this reason, the determination of 11‐nor‐9‐carboxy‐Δ-9-tetrahydrocannabinol (THC‐COOH) has been proposed by the Society of Hair Testing (SoHT) in order to prove active cannabis consumption. The identification of THC-COOH in hair will continue to be complicated by its acidic nature and the critical low concentration due to the preferential incorporation of basic compounds into hair shaft. Alternatively, 11-OH-THC may be considered as a complementary marker for THC administration. Our recent study reported an accurate validated procedure for THC, CBD, CBN and 11-OH-THC in hair, based on a GC/MS-MS method in electron ionization mode. However, unlike THC-COOH, a cut-off level for 11-OH-THC in hair has not been fixed yet. For this reason, the aim of this study is to propose a concentration value for 11-OH-THC in hair analysis in order to discriminate between chronic use and external contamination. Receiver operating characteristics (ROC) analysis was applied for cut‐off evaluation after 11-OH-THC quantification in a pool of 672 THC-positive hair samples. Results have shown a concentration range between 0.01–5.34 ng/mg for THC (mean 0.34 ng/mg, median 0.12), 0.00–19.2 pg/mg for THC-COOH (mean 0.72 pg/mg, median 0.19 pg/mg) and 0.01–13.33 ng/mg for 11-OH-THC (mean 1.09 ng/mg, median 0.51 ng/mg) for scalp hair and between 0.03–6.32 ng/mg for THC (mean 0.82 ng/mg, median 0.30), 0.00–42.1 pg/mg for THC-COOH (mean 2.70 pg/mg, median 1.08 pg/mg) and 0.00–7.88 ng/mg for 11-OH-THC (mean 1.70 ng/mg, median 0.89 ng/mg) for body hair. Considering these experimental data collected in our laboratory, we propose a cut-off level of 0.5 for scalp and body hair, as indicative of cannabis active consumption. The ROC curve AUCs for 11-OH-THC were 0.873 and 0.884 in 590 scalp hair and 82 body hair samples, respectively. The comparison of the results for THC-COOH (control method) and 11-OH-THC (test method) was also made by means of the Cohen's kappa statistics providing a good agreement according to both Landis & Koch and Fleiss scales. Additionally, we suggest that the detection of both THC-COOH and 11-OH-THC should be mandatory in order to prove active intake and exclude false positive results from external contamination.